A prospective analysis of the injury incidence of young male professional football players on artificial turf - Bianco, A.; Spedicato, M.; Petrucci, M.; Messina, G.; Thomas, E.; Sahin, F. N.; Paoli, A.; Palma, A. (Asian Journal of Sports Medicine, 2016)
Background: The effects of synthetic surfaces on the risk of injuries is still debated in literature and the majority of published data seems to be contradictory. For such reasons the understanding of injury incidence on such surfaces, especially in youth sport, is fundamental for injury prevention.